Representing theories of change: technical challenges with evaluation consequences - Davies, Rick (Journal of Development Effectiveness, 2018)
This paper looks at the technical issues associated with the represent ation of Theories of Change and the implications of design choices for the evaluability of those theories. The focus is on the description o f connections between events rather than the events themselves, becaus e this is seen as a widespread design weakness. Using examples and evi dence from Internet sources six structural problems are described alon g with their consequences for evaluation. The paper then outlines a ra nge of different ways of addressing these problems that could be used by programme designers, implementers and evaluators. The paper conclud es with some caution speculating on why the design problems are so end emic but also pointing a way forward. Four strands of work are identif ied that CEDIL and DFID could invest in to develop solutions identifie d in the paper.
Keywords: Evaluation; evaluability; representation; theory of change